2017
DOI: 10.1039/c7ob00176b
|View full text |Cite
|
Sign up to set email alerts
|

A decade of DNA-hybrid catalysis: from innovation to comprehension

Abstract: In a little over a decade, the unique chirality of oligonucleotides has allowed the development of a variety of asymmetric synthetic transformations. The concept lies in embedding an achiral transition metal catalyst in a DNA double helix, which provides the necessary chiral microenvironment to selectively form one enantiomer of a given reaction product. The most recent efforts at unveiling new reactivities have been accompanied by the desire to understand the mechanisms by which the chirality is transferred a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 99 publications
0
29
0
Order By: Relevance
“…High endo/exo selectivities were obtained (up to 98/2 in favour of the endo product) albeit moderate enantioselectivities (up to 53 % ee ). Nonetheless, these results demonstrated that the DNA double helix could be used as a powerful source of chirality in the context of asymmetric catalysis …”
Section: Dna‐based Asymmetric Catalysismentioning
confidence: 70%
See 1 more Smart Citation
“…High endo/exo selectivities were obtained (up to 98/2 in favour of the endo product) albeit moderate enantioselectivities (up to 53 % ee ). Nonetheless, these results demonstrated that the DNA double helix could be used as a powerful source of chirality in the context of asymmetric catalysis …”
Section: Dna‐based Asymmetric Catalysismentioning
confidence: 70%
“…Nonetheless, these results demonstrated that the DNA double helix could be used as a powerful source of chirality in the context of asymmetric catalysis. [41] A follow-up investigation evaluating the influence of the achiral ligand allowed Roelfes and co-workers to identify commercially available 4,4'-dimethyl-2,2'-bipyridine L3 as an efficient and simpler alternative to L1 and L2 leading to an almost complete endo selectivity (endo/exo = 99 : 1) and excellent enantioselectivities (99 % and 98 % ee at 30 and 5 mol% catalyst loading respectively. [42] Interestingly, similar results were also obtained on β-aryl-substituted α,β-unsaturated acyl imidazoles ( Figure 4).…”
Section: Natural Dna-helixmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] The chiral framework and space generated by such a double-helical structure have the potential for developing unique and conceptually new supramolecular asymmetric catalyses, 10,11 but successful examples are quite limited until now [12][13][14][15][16] except for the DNA-based catalysts. 17,18 Here, we show the invaluable role of a complementary double-helical framework with a controlled helicity for supramolecular bifunctional asymmetric organocatalysis. The design and synthesis of complementary double-helical bifunctional organocatalysts is based on our modular strategy using m-terphenyl-based complementary double helices stabilized by chiral amidiniumachiral carboxylate salt bridges.…”
Section: Introductionmentioning
confidence: 87%
“…Although a variety of optically active single‐stranded helical polymers and supramolecular helical assemblies with specific functions, such as asymmetric catalysis and chiral recognition, has been developed during the past three decades, those one‐handed double helices reminiscent of the natural DNA double helix still remain a challenge regarding their synthesis, structures, and functions . The chiral framework and space generated by such a double‐helical structure have the potential for developing unique and conceptually new supramolecular asymmetric catalyses, but successful examples are quite limited until now except for the DNA‐based catalysts …”
Section: Introductionmentioning
confidence: 99%
“…Chiro‐selective catalysis based on DNA nanostructures has been extensively studied and is mostly based upon the introduction of a transition metal catalyst in close proximity with a DNA double helix. The DNA produces the chiral environment necessary for asymmetric catalysis while the catalytic metal ion is linked to the DNA with different strategies, generating products with an enantiomeric excess as high as 99% for certain reactions.…”
Section: Strategiesmentioning
confidence: 99%